Drosophila acinus encodes a novel regulator of endocytic and autophagic trafficking. - Haberman, A.S.; Akbar, M.A.; Ray, S.; Krämer, H. (Development, 2010)
Endosomal trafficking affects many cellular pathways from cell signaling to metabolism, but little is known about how these effects are coordinated. In a genetic screen for mutants affecting endosomal trafficking, we identified Drosophila acinus (dacn; hook-like). Its mammalian homolog Acinus has been implicated in RNA processing and chromatin fragmentation during apoptosis. Loss-of-function analysis of dacn revealed two distinct functions. First, dacn is required for stabilization of early endosomes, thus modulating levels of Notch and Egfr signaling. Second, loss of dacn interferes with cellular starvation responses by inhibiting autophagosome maturation. By contrast, overexpression of dacn causes lethality due to enhanced autophagy. We show that this enhanced autophagy is independent of the Tor pathway. Taken together, our data show that dacn encodes a regulator of endosomal and autophagosomal dynamics, modulating developmental signaling and the cellular response to starvation.